2022
DOI: 10.1002/htj.22780
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental study of a shell and tube heat exchanger for different baffles

Abstract: In the present work, the shell and tube heat exchanger (STHX) is designed based on The Tubular Exchanger Manufacturers Association standards with hot fluid (water) flowing on the shell side and cold fluid on the tube side. A comparison is made between the Nusselt number and friction factor obtained from numerical and experimental results of segmental baffles (SBs) and helical baffles (HB) with different baffle inclinations. The results show that SB provided a higher Colburn factor (j s ) when compared with HBs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
(90 reference statements)
0
5
0
Order By: Relevance
“…And the effect of volume flow rate on HT is more at high rates and vice versa. Aparna et al 17 They also observed that as the inclined angle increases up to 30°, the performance evaluation criterion (PEC) remains constant, and PEC decreases with further increasing angle. Liu et al 19 experimentally studied the forced convection and HT in non-Newtonian two-phase ethyleneglycol/H 2 O nanofluid through a wavy-sinusoidal in turbulent flow with uniform temperature.…”
Section: Nanofluidsmentioning
confidence: 93%
See 3 more Smart Citations
“…And the effect of volume flow rate on HT is more at high rates and vice versa. Aparna et al 17 They also observed that as the inclined angle increases up to 30°, the performance evaluation criterion (PEC) remains constant, and PEC decreases with further increasing angle. Liu et al 19 experimentally studied the forced convection and HT in non-Newtonian two-phase ethyleneglycol/H 2 O nanofluid through a wavy-sinusoidal in turbulent flow with uniform temperature.…”
Section: Nanofluidsmentioning
confidence: 93%
“…And the effect of volume flow rate on HT is more at high rates and vice versa. Aparna et al 17 experimentally and numerically studied the STHX by varying shell side fluid mass flow rate using the TEMA standard and found the Colburn factor for different helical baffles (20°, 30°, 40°, and 50°).…”
Section: Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…They typically modify the flow channel's surface or geometry or contain an insert, substance, or device. Researchers have utilized a variety of passive techniques to boost the rate of heat transmission in a variety of thermal devices, including the use of rough surfaces, 24,25 porous materials, 26 inserts, [27][28][29][30][31] extended surfaces, [32][33][34][35][36][37][38] displaced enhancement devices (coil/helical/ spiral tube), 39,40 nanofluids, [41][42][43][44] and so on.…”
Section: Passive Techniquesmentioning
confidence: 99%